Technical report: Characteristics of silage based on sweetpotato with combinations of local feed resources in Uganda. - Mutetika, D.; Ojakol, J.F.; Lule, Peter M.; Naziri, D.; Kyalo, Gerald; Pezo, Danilo A.; Lukuyu, Ben A. (2017)
A study to determine the characteristics and chemical composition of different silages based on sweetpotato vines in combination with several local feed resources was conducted in the Animal Science laboratory at the Makerere University Agricultural Research Institute, Kabanyolo (MUARIK). Sweetpotato vines from variety NASPOT 11 were used. Maize bran and cassava root were used as ferment starters (additives) during the ensiling process. The silages were analyzed for pH, moisture content, crude protein, neutral detergent fiber, ether extracts and ash, calcium and phosphorus. The results showed that sweetpotato vines can produce silage of acceptable quality even when no external ferment starter is added. However, addition of a solid ferment starter like maize bran served to absorb the moisture that would accumulate as effluent at the bottom of the silo and eventually lead to spoilage. The dry matter content of the silage was low (> 24%) and would not meet the requirements of young growing pigs. The resultant silage had crude protein content higher than 19 percent and would meet the requirements for growing pigs except for the balance of essential amino acids and low dry matter of the material. For efficient utilization, feeding sweetpotato silage diets would require supplementation to satisfy requirements for dry matter and essential amino acids.